CORRELATIONS OF CADMIUM EXPOSURE WITH THE UREUM AND CREATININE SERUM LEVELS IN BATURADEN ORNAMENTAL PLANT FARMERS - Nafiisah, Nafiisah; Laksana, Agung Saprasetya Dwi; Mulyanto, Joko (Biomedika, 2020)
ABSTRACT  Baturaden ornamental plant farmers use pesticides and fertilizers containing cadmium to increase growth and plant diseases control. Cadmium is a very toxic heavy metal. Small doses of cadmium exposure in over a long time through respiratory tract, digestion, and skin penetration causes a workload on the kidneys. It resulting kidney damage that characterized by increased ureum and creatinine serum levels. The aimed of this study was determine the correlation of cadmium exposure to kidney function in terms of urea and creatinine serum levels. The research design was an observational analytic approach with cross sectional method. The respondents were 43 farmers. Research data were collected by interviews, measured the  urea and creatinine serum levels, also the cadmium urine levels. Data were analyzed by Spearman test. The results showed that there was a weak significant correlation between cadmium urine to ureum (r= 0.399 and p= 0.008) and creatinine serum levels (r= 0.331 and p= 0.03). We concluded that cadmium exposured correlated with increased ureum and creatinine serum levels.Keywords: Cadmium, Urea Serum Level, Creatinine Serum Level, Ornamental Plant Farmers                                                                                                       ABSTRAK Petani tanaman hias di Baturaden menggunakan pestisida dan pupuk yang mengandung kadmium untuk meningkatkan pertumbuhan dan pengendalian penyakit tanaman. Kadmium adalah logam berat yang sangat beracun. Paparan kadmium dosis kecil dalam jangka waktu yang lama melalui saluran pernafasan, pencernaan, dan penetrasi kulit menyebabkan beban kerja pada ginjal. Hal tersebut mengakibatkan kerusakan ginjal yang ditandai dengan peningkatan kadar ureum dan kreatinin serum. Penelitian ini bertujuan untuk mengetahui hubungan paparan kadmium terhadap fungsi ginjal ditinjau dari kadar ureum dan kreatinin serum. Desain penelitian adalah observasional analitik dengan metode cross sectional. Respondennya sebanyak 43 petani. Pengumpulan data penelitian dilakukan dengan wawancara, pengukuran kadar urea dan kreatinin serum, serta kadar kadmium urin. Data dianalisis dengan uji Spearman. Hasil penelitian menunjukkan bahwa terdapat hubungan bermakna yang lemah antara kadar kadmium urin dengan kadar serum ureum (r= 0,399 dan p= 0,008) dan kreatinin (r= 0,331 dan p= 0,03). Kami menyimpulkan bahwa paparan kadmium berkorelasi dengan peningkatan kadar ureum dan kreatinin serum.Kata Kunci: Kadmium, Kadar Ureum Serum, Kadar Kreatini Serum, Petani Tanaman Hias